Geographic Range and Body Size Influence Abundance Patterns in Reef Fishes - M. F. Maxwell; D. R. Barneche; R. Divieso; S. R. Floeter; O. J. Luiz; A. L. Luza; M. R. Pie; A. C. Siqueira; M. G. Bender (Journal of Biogeography, 2026)
Aim Understanding how body size and geographic range size influence species abundance is central to macroecology. Here, we characterized these relationships for reef fishes, the world's most diverse vertebrate group, across global and regional scales. Location Global tropical and subtropical reefs. Time Period Current. Major Taxa Studied Reef‐associated fishes. Methods We compiled a comprehensive dataset on abundance, body size and geographic range size for 828 reef fish species. Abundance was measured as density (ind/m 2 ) using transect‐based observational data. To analyse global‐scale patterns, we applied Bayesian quantile regressions and Bayesian phylogenetic regressions to account for phylogenetic relatedness. We also used Bayesian phylogenetic regressions at the regional scale, considering body size, geographic range size and sampled transect area as marginal effects. Results The relationship between geographic range size and body size exhibited a slightly triangular pattern, where large‐bodied species tended to have broad range sizes, whereas small‐bodied species varied in range sizes. We found a negative relationship between species abundance and body size, and a dual relationship (i.e., both negative and positive) between species abundance and geographic range size: species with restricted ranges were either rare or abundant, whereas widely distributed species had intermediate abundance. Similar patterns were observed across marine realms, with abundance decreasing with body size and presenting a dual relationship with geographic range size. Main Conclusions Our findings reveal that body size and geographic range size are important correlates of reef fish abundance, but their effects vary across spatial scales. These results provide new insight into macroecological processes influencing reef fish diversity and distribution.